Diphenhydramine increases the therapeutic window for platinum drugs by simultaneously sensitizing tumor cells and protecting normal cells - Melnikova, Margarita; Wauer, Ulrike Sophie; Erdmann, Kati; Wimberger, Pauline (Molecular oncology, 2020)
Platinum-based compounds remain a well-established chemotherapy for cancer treatment despite their adverse effects which substantially restrict the therapeutic windows of the drugs. Both the cell type-specific toxicity and the clinical responsiveness of tumors have been associated with mechanisms that alter drug entry and export. We sought to identify pharmacological agents that promote cisplatin (CP) efficacy by augmenting the levels of drug-induced DNA lesions in malignant cells and simultaneously protecting normal tissues from accumulating such damage and from functional loss. Formation and persistence of platination products in the DNA of individual nuclei were measured in drug-exposed cell lines, in primary human tumor cells and in tissue sections using an immunocytochemical method. Using a mouse model of CP-induced toxicity, the antihistaminic drug diphenhydramine (DIPH) and two methylated derivatives decreased DNA platination in normal tissues and also ameliorated nephrotoxicity, ototoxicity, and neurotoxicity. In addition, DIPH sensitized multiple cancer cell types, particularly ovarian cancer cells, to CP by increasing intracellular uptake, DNA platination, and/or apoptosis in cell lines and in patient-derived primary tumor cells. Mechanistically, DIPH diminished transport capacity of CP efflux pumps MRP2, MRP3, and MRP5 particularly in its C2+C6 bimethylated form. Overall, we demonstrate that DIPH reduces side effects of platinum-based chemotherapy and simultaneously inhibits key mechanisms of platinum resistance. We propose that measuring DNA platination after ex vivo exposure may predict the responsiveness of individual tumors to DIPH-like modulators.
Gesehen am 24.06.2020